2017
DOI: 10.2147/vhrm.s134669
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived health-related quality of life before and after laparoscopic aortobifemoral bypass

Abstract: BackgroundIn patients operated with laparoscopic aortobifemoral bypass (LABFB) for atherosclerotic obstruction in aortoiliac segment, the main focus of the reports published during the last two decades has been morbidity and mortality. The primary objective of this study was to examine the health-related quality of life (HRQL) in these patients before and after LABFB.Patients and methodsFifty consecutive patients (27 females) with Trans-Atlantic Inter-Society Consensus II, type D lesions were prospectively inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In other patient groups, it has been shown that the benefits of laparoscopic surgery are mostly gained during the first year, 38 , 43 , 44 In our pilot study, the main effect on HRQoL was during the first 6 months. 14 Even if the difference between the 2 groups would later during follow-up decrease, there is no indication that the benefits in terms of HRQoL and spared economic costs will be in favor of other than LABF. There also seem to be no negative long-term effects of LABF for AIOD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other patient groups, it has been shown that the benefits of laparoscopic surgery are mostly gained during the first year, 38 , 43 , 44 In our pilot study, the main effect on HRQoL was during the first 6 months. 14 Even if the difference between the 2 groups would later during follow-up decrease, there is no indication that the benefits in terms of HRQoL and spared economic costs will be in favor of other than LABF. There also seem to be no negative long-term effects of LABF for AIOD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our cohort study, we expected a gain in HRQoL during the first 6 months and similar results in the 2 groups thereafter. 13 , 14 The patients answered the EuroQol EQ-5D-5L questionnaire at 4 different time points; before surgery (baseline), and at 1, 3 and 6 months postoperatively. 30 , 31 The costs included in this study are the cost of surgical equipment, prosthesis and the costs related to the hospital stay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOS 36-item short form health survey (SF-36) has been used world-wide as a generic and coherent measure to assess HRQoL in patients and residents [ 8 10 ]. More than 40 translated versions have been applied around the world [ 11 ] and it is the standard for international quality of life assessment.…”
Section: Introductionmentioning
confidence: 99%